Controlled Growth and Up‐Conversion Improvement of Sodium Yttrium Fluoride Crystals (Eur. J. Inorg. Chem. 8/2013). Issue 8 (11th March 2013) - Fu, Junxiang; Fu, Xionghui; Wang, Chaomin; Yang, Xianfeng; Zhuang, Jianle; Zhang, Gongguo; Lai, Boyuan; Wu, Mingmei; Wang, Jing
Abstract : The cover picture shows that hexagonal crystals of sodium yttrium fluoride can exhibit significantly enhanced up‐conversion emission after the topotactic insertion of more sodium cations into the channels, during which both the structure of the crystals and the morphology of the material remain unchanged. Details are discussed in the article by M. Wu, J. Wang et al. on p. 1269ff.